Stability of diagnostic assessment for autism spectrum disorder between 18 and 36 months in a high‐risk cohort. Issue 7 (27th November 2015) - Zwaigenbaum, Lonnie; Bryson, Susan E.; Brian, Jessica; Smith, Isabel M.; Roberts, Wendy; Szatmari, Peter; Roncadin, Caroline; Garon, Nancy; Vaillancourt, Tracy
Abstract : Children with autism spectrum disorder (ASD) are diagnosed, on average, around the age of 4 years. However, previous research has shown that the diagnosis can be made as early as 2 years, and that if the child is seen a year or more later, it is highly likely that the diagnosis will be confirmed. In this study, to examine whether diagnoses made as early as 18 months of age are also "stable, " we followed a group of younger siblings of children with ASD (who are known to be at higher risk). We also examined whether the age of ASD diagnosis within this high‐risk group was related to the severity of children's ASD symptoms or developmental delays. Participants ( n = 381) were seen at three ages: 18 months, 24 months, and 3 years. ASD symptoms, general development, and adaptive functioning were assessed at each time point. Twenty‐three children were diagnosed with ASD at 18 months and a total of 61 at 24 months. Of these diagnoses, 19/23 (82.6%) and 56/61 (91.8%), respectively, were confirmed independently at 3 years. However, 45 children were diagnosed with ASD at 3 years who had not been identified at earlier visits. Children diagnosed at 18 months, in comparison to those diagnosed at 24 months, had less advanced language and adaptive skills at 18 months. Children not diagnosed with ASD until 3 years, compared with those diagnosed earlier, had more advanced language and adaptive skills, and milder ASD symptoms. Autism Res 2016, 9: 790–800 . © 2015 International Society for Autism Research, Wiley Periodicals, Inc.